Microstructures and Mechanical Properties of Commercial Hot‐Extruded Copper Processed by Torsion Deformation1 . Issue 10 (22nd July 2016) - Guo, Ning; Li, Xiaoxia; Xiao, Mei; Xin, Renlong; Chai, Linjiang; Song, Bo; Yu, Hongbing; Li, Lu
Abstract : Free‐end torsion deformation is used for processing copper rod in this work. Both microstructures and mechanical properties of the torsional rods are quantitatively analyzed. The results show that gradient lamellar dislocation substructures (LDS) along the radial direction as the main defects are formed after torsion. The increment of the LDS density, the shrinking of spacing size, and the change of length/spacing (L/S) ratio of the LDS are all non‐monotonic function of torsion revolution. High‐density LDS with fine spacing can retain strain hardening capability, which results in good combination of high tensile strength and good ductility in the torsional deformed sample with large number of revolutions. The influence of torsion strain on primary twin boundaries (TBs) in the hot‐extruded rod is also discussed. Abstract : Free‐end torsion deformation is used for processing copper rod in this work . Results show that the torsional rod has a gradient microhardness from core to surface due to a gradient distribution of lamellar dislocation substructures (LDS). With increasing torsion revolutions, the LDS density increases gradually, resulting in the improvement of subsequent tensile strength and hardening capability.